Non-catalytic synthesis of boron carbide (B4C) nano structures with various morphologies by sol-gel process - Avcioglu, Suna; Kaya, Figen; Kaya, Cengiz (ELSEVIER, 2019)
Non-catalytic synthesis of boron carbide (B4C) powders with various morphologies is presented by sol-gel technique using boric acid, glycerol, and citric acid as starting materials. The effect of composition and processing conditions on the phase assembly, particle size and morphology of boron carbide powders were investigated. The formation of nanobelt, needle like, and polyhedral-equiaxed boron carbide particles with a wide-ranged particle size distribution in between 50 nm and 100 mm were observed after heat treatment at 1300 degrees C for 5 h in argon atmosphere. Furthermore, rod, plate and rhomboid-flake like boron carbide structures were produced by using relatively higher heat treatment temperature of 1500 degrees C. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Boron carbide; Sol-gel preparation; Heat treatment; Particle morphology; Nanoparticles; POWDER; ACID; TEMPERATURE; Materials Science; Physics